Motivasi dan Tantangan Menjadi Wirausaha (Studi Kuantitatif pada Mahasiswa UNIPMA) - Septyana Luckyta Sari (UNIVERSITAS PGRI MADIUN, 2021)
Data Badan Pusat Statistik for August 2020 recorded that 138.22 million Indonesians are in the workforce, the unemployment rate reached 7.07%. The high number of unemployed hinders economic growth. So Indonesia must increase the number of entrepreneurs. This problem encourages the government to cooperate with Kementerian Riset dan Perguruan Tinggi to apply entrepreneurship courses in education curriculum. The program and its mechanisms are expected to encourage economic growth in Indonesia and create many jobs. The research objective was to determine the entrepreneurial perceptions of sixth semester management students of Universitas PGRI Madiun. This research is supported by various factors such as motivators, challenges and government support to start and maintain new businesses. This study also tries to see whether there are differences between gender, educational background, parents, and work experience as demographic factors with one's entrepreneurial intentions. This research uses quantitative methods. Data collection using google form link questionnaire which was distributed to 337 students through class leaders. The data analysis used was descriptive statistics. The results of this study indicate that students of Universitas PGRI Madiun have a high enough intention to become entrepreneurs. Their greatest motivation is to increase income opportunities. Meanwhile, what is considered the biggest challenge in becoming an entrepreneur is funding. So, government support that is deemed urgently needed is to provide financial assistance.